Prediction of diacerein inhibition activity against interleukin-1 receptors through docking method and tracing of pharmacokinetic profiles and their toxicity - Frengki Frengki; Vivi Sofia; Deddi Prima Putra; Fatma Sri Wahyuni; Daan Khambri; Henni Vanda (Universitas Ahmad Dahlan, 2020)
IL-1 is one of the cytokines involved in joint diseases such as osteoarthritis. IL-1 plays a role in maintaining the balance of proteolytic proteins:MMPs and TIMPs inhibitors. Increased expression and uncontrolled IL-1 activity tend to increase the role of MMPs in degrading proteoglycans and joint tissue collagen. This study aims to reveal the interaction model of one of the osteoarthritis drugs, namely diacerein. A drug belongs to a group of disease-modifying osteoarthritis drugs (DMOADs) to suppressthe development of the disease rate, improving the structure and function of the cartilage and surrounding tissue.